1999
DOI: 10.1074/jbc.274.28.19670
|View full text |Cite
|
Sign up to set email alerts
|

Human Tryptases α and β/II Are Functionally Distinct Due, in Part, to a Single Amino Acid Difference in One of the Surface Loops That Forms the Substrate-binding Cleft

Abstract: Tryptases ␣ and ␤/II were expressed in insect cells to try to ascertain why human mast cells express these two nearly identical granule proteases. In contrast to that proposed by others, residue ؊3 in the propeptide did not appear to be essential for the three-dimensional folding, post-translational modification, and/or activation of this family of serine proteases. Both recombinant tryptases were functional and bound the active-site inhibitor diisopropyl fluorophosphate. However, they differed in their abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
1
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 37 publications
4
73
1
1
Order By: Relevance
“…They have been implicated in asthma and other allergy disorders. Secreted as catalytically active, noncovalently bound tetramers, there are at least four closely related tryptases: ␣, ␤I, II, and III, sharing at least 93% identical amino acid sequences (40). Human lung tryptase (␣) showed a preference for the polar amino acids Asn, Ser, and Thr in the P 2 position for both the P 1 ϭ Arg and Lys sublibraries (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They have been implicated in asthma and other allergy disorders. Secreted as catalytically active, noncovalently bound tetramers, there are at least four closely related tryptases: ␣, ␤I, II, and III, sharing at least 93% identical amino acid sequences (40). Human lung tryptase (␣) showed a preference for the polar amino acids Asn, Ser, and Thr in the P 2 position for both the P 1 ϭ Arg and Lys sublibraries (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is highly unlikely that these two human tryptases are functionally identical in vivo. Using an expression/site-directed mutagenesis approach, we demonstrated that the ability of recombinant tryptase ␣ to cleave fibrinogen and various colorimetric substrates in vitro differs from that of other mouse and human tryptases due, in part, to a single Asp/Gly difference in loop 2 (33). Neutrophils express PAR2 and can be activated by trypsin and PAR2 receptor agonists (57), and the constituents of this cell's secretory granules contribute to airway hyperreactivity in various in vivo model systems of inflammation (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…Expression constructs were then prepared that encode pseudo-zymogen forms of these two tryptases that both have a 5-residue enterokinase-susceptible peptide between the natural propeptide and the mature portion of the enzyme and an 8-residue FLAG peptide attached to the C terminus. The resulting cDNAs were subcloned into the expression vector pVL1393, and the recombinant pseudo-zymogens were expressed in baculovirus-infected High Five ® insect cells as previously described for human tryptase ␣, mMCP-6, and mMCP-7 (25,26,33). After their purification, the mature forms of the two human tryptases were obtained by proteolytic removal of the bioengineered propeptides.…”
Section: Generation Of Recombinant Human Tryptases ␣ and ␤I And Analymentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that they each perform different proteolytic functions that may be reflected in their substrate specificity preferences. Indeed, it has recently been shown that a single amino acid substitution between tryptase ␣ and tryptase ␤II accounts for discrimination in substrate preference for the two enzymes (9).…”
mentioning
confidence: 99%